A Transition‐Metal‐Free Synthesis of Fluorinated Naphthols. Issue 22 (25th April 2014) - Hammann, Jeffrey M.; Unzner, Teresa A.; Magauer, Thomas
Abstract Herein, we describe a transition‐metal‐free protocol for the conversion of simple 2‐allyl‐3‐(trifluoromethyl)phenols into substituted 5‐fluoronaphthalen‐1‐ols. The key events of this reaction include the selective activation of two CF bonds and formation of an intermediate hexatriene system, which undergoes a 6π electrocyclization, followed by rearomatization. This concept enables the rapid conversion (three steps) of various commercially available 3‐(trifluoromethyl)phenols into novel fluorine‐containing naphthols, which are difficult to prepare by previous methods. The reported sequence was also extended to a one‐pot transformation of 3‐(trifluoromethyl)phenols into 5‐fluoronaphthalen‐1‐ols.